HUBUNGAN HARGA DIRI DENGAN KESEJAHTERAAN PSIKOLOGIS PADA REMAJA KORBAN BULLYING VERBAL - Rizka Yunita; Widya Addiarto (STIKes Maharani Malang, 2022)
Introduction:Verbal bullying is a form of violent behavior that often occurs in adolescents. Verbal bullying is done by saying using harsh sentences, mocking, even cursing. Verbal bullying can have a negative effect on its victims, such as causing fear, anxiety, worry and even lowering self-esteem. This situation can weaken the self-ability of the bullying victim so that the victim is unable to develop himself, the impact is that the victim experiences feelings of doubt in achieving his life goals and feels unhappy. This condition shows that the victim has decreased psychological well-being. This study aims to analyze self-esteem with psychological well-being of victims of verbal bullying. Method:The research design used descriptive analytic with a cross sectional study approach. The population of this study were the students of Pondok Hafshawaty Zainul Hasan Islamic Boarding School as many as 62 people who experienced verbal bullying victims. The research sampling technique used purposive sampling so that the research sample obtained was the students of Pondok Hafshawaty Zainul Hasan Islamic Boarding School as many as 54 people who experienced verbal bullying victims according to the inclusion and exclusion criteria. The research instrument used a questionnaire. Data analysis using Spearman Rank test. Result and analysis: The results showed that the ρ value of 0.002 indicates that there is a significant relationship between self-esteem and psychological well-being of victims of verbal bullying. Verbal bullying can have a negative impact on the victim, so there needs to be participation, especially peers and schools in order to reduce the frequency of bullying. Keywords: bullying, victim, self-esteem, psychological well-being